PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PT. DAVINDO ANUGERAH SEMESTA - SELLY SEPTIANA; WASIMAN . (LP2MTBM MAKARIOZ, 2020)
The development of communication technology in Indonesia is increasingly sophisticated in the lives of people who use itand cannot be avoided. By paying attention to the promotions given to customers and the good quality of service provided bythe company to consumers so as to create customer satisfaction. This study aims to determine the effect of promotion oncustomer satisfaction, the effect of service quality on customer satisfaction and the effect of promotion and service quality oncustomer satisfaction and the object of research is PT Davindo Anugerah Semesta Testing is done using classicalassumption tests, influence tests and partial hypothesis testing with t test and simultaneously with the f test. The results ofthe research stated that partially the promotion had a significant effect on customer satisfaction and the quality of service hada significant effect on customer satisfaction and simultaneously promotion and service quality together had a significanteffect on customer satisfaction of PT Davindo Anugerah Semesta products.